Konsep Sembah dan Budi Luhur dalam Ajaran Mangkunagara IV dan Relevansinya dengan Hadis Nabi - Siti Mujibatun (IAIN Ponorogo, 2013)
Abstract: Islamic teachings spread in Indonesia, especially in Java, when the Mangkunegara IV authority, through its mysticism (Sufism) teaching, was adjusted to the religious teachings and beliefs containing moral values and character building inspired by thinking paradigm of cultural values of Javanese (Kejawen). This indicates that development of Islam in Indonesia has been strongly influenced by Islamic mysticism, especially, of Javanese culture. It can be seen from literature of Javanese Islamic teaching. Some identities and characteristics of Javanese teachings that still survive up to now are the principle teachings of worship to God and good deed. Both principles are relevant to the teachings of Qur’an and hadith. These teachings were also practiced by Sunni mysticism such as al-Ghazali and non-Sunni mysticism like Al-Hallaj and Ibn ‘Arabi. Additionally, in Indonesia, specially in Java, the absorption process of Islamic teachings can not be separated from the influence of Javanese culture which contains religious values of Sufism teachings. The concept of worship and good deed is done by the mysticism doers both by Sunni and non-Sunni followers.